STRES DAN KEJADIAN PERIODONTITIS (KAJIAN LITERATUR) - Nadia Quamilla (Journal of Syiah Kuala Dentistry Society, 2016)
AbstractStress is a putative risk factor for periodontitis. Previous research has shown that stress couldinfluence the extent and severity periodontitis. This article was aimed to study the corelationbetween stress and periodontitis. Periodontitis is a chronic inflammatory disease caused byinfection on supporting tissues of the teeth. The clinical diagnosic of periodontitis is based onmeasures of the presence periodontal pocket, loss of clinical attachment, loss of alveolar boneor combination of these measures. Etiologic of periodontitis is plaque and calculus. Stress is aputative risk factor for periodontitis. Previous research has shown that stress could influencethe extent and severity periodontitis. It can be concluded that in this study, there wasrelationship between stress and periodontitis.Keywords : stress, periodontitis, periodontal pocket